The Copyright Responsibilities of Artificial Intelligence in the Digital Age - Cantika Aulia; Egi Nugraha; Raja Benhard Parlindungan (Universitas Muhammadiyah Malang, 2023)
The development of the times facilitates the dissemination of information and culture to various parts of the world. The law is one of the things that also developed. The law cannot be separated from the regulation regarding intellectual property rights that participate in developing as technology and globalization develop. As regulations in Indonesia, one type of intellectual property rights is copyright. In digital development, technology is also developed, one of which is artificial intelligence. In its development Artificial Intelligence is developing very rapidly even today Artificial Intelligence can make artwork in the form of digital photos that can be protected by copyright. This study was compiled through a conceptual approach and using normative legal research methods, doctrinal, and comparative studies, as well as using quality analysis techniques. This study argues that Indonesia has not accommodated the arrangement of artificial intelligence results so that the arrangement is needed so as to create a law that is able to follow the flow of times and create protection against artificial intelligence creations. Abstrak Perkembangan zaman mempermudah penyebaran informasi mupun budaya ke berbagai penjuru dunia. Hukum menjadi salah satu hal yang ikut berkembang pula. Hukum tidak mungkin terlepas dari pengaturan mengenai Hak Kekayaan Intelektual yang ikuts mengalami perkembangan seiring berkembang teknologi dan globalisasi. Sebagaimana pengaturan di Indonesia, salah satu jenis Hak Kekayaan Intelektual adalah Hak Cipta. Dalam perkembangan digital, berkembang pula teknologi salah satunya Artificial Intellengence. Dalam perkembangannya Artificial Intellegence berkembang sangat pesat bahkan dewasa ini Artificial Intellegence dapat membuat karya seni berupa foto digital yang bisa dilindungi Hak Cipta. Penelitian ini dibuat melalui pendekatan konseptual dan menggunakan metode penelitian hukum normatif, doktrinal, dan studi perbandingan, serta menggunakan teknik analisis kualitas. Penelitian ini berpendapat bahwa Indonesia belum mengakomodir pengaturan mengenai karya seni hasil Artificial Intelligence sehingga dibutuhkan pengaturan tersebut sehingga tercipta hukum yang mampu mengikuti arus zaman dan tercipta perlindungan terhadap karya kreasi Artificial Intelligence.